ALISIS KEMAMPUAN MEMPRESENTASIKAN KARYA ILMIAH SECARA ORAL MAHASISWA PROGRAM STUDI BAHASA INGGRIS FKIP UNIVERSITAS RIAU (Proceeding 7th International Seminar on Regional Education, 2015)
AbstracThe objective of this study is to create a learning model of presenting scientific article in Seminar on ELT as a subject. The population of the study are 29 students who took Seminar on ELT at 2014/2015 academic year. The technique of collecting data is to record the studentsâ oral presentation of scientific article in Seminar on ELT which cover pronunciation, grammar, vocabulary, fluency, and comprehension. The collected data were analyzed by giving scores based on each component criteria. The research findings are as follows: pronunciation (41%) in category of 3 (foreign accent required), grammar (58.62%) in category of 4 (occasional errors), vocabulary (44.82%) in category of 4 (professional vocabulary), fluency (51.71%) in category of 5 (effortless and smooth speech), and comprehension (41.37%) in category of 4 (quite well normal educated speech). In conclusion, the majority of the studentsâ ability in oral presentation of scientific article are in the category of 4 among five components of oral presentation. The implication of the findings are those of the presentation components should be well taught in Speaking and Seminar on ELT classes.Keywords: Oral Presentation of Scientific Article, Speaking and Seminar on ELT